The Great Exaptation. Around the fundamental idea of evolutionary psychology - Reuter, Magdalena (Ecological questions, 2010)
The subject of this article is to study the critique of the adaptationist programme in the evolutionary psychology. I focus on the issue how the notions of “spandrel” and “exaptation”, first introduced to evolutionary biology by S. J. Gould, R. Lewontin and E. Vrba, were then applied to the field of evolutionary psychology and to more broadly evolution of human cognitive processes. My aim is to show, that these terms are differently applied to various kinds of investigations in the field of the evolution of human mind. I show that not only the orginal definitional issues are problematic but also the application of these terms to evolution of human mind can be confusing. I try to put the main issues in order on that matter and propose the solutions to these confusions. I propose the methodological assumptions that should be accepted to the theory of spandrels and exaptations.